PENERAPAN MODEL PEMBELAJARAN SAINS TEKNOLOGI MASYARAKAT DENGAN METODE SAINTIFIK UNTUK MENINGKATKAN KEMAMPUAN LITERASI SAINS SISWA PADA PEMBELAJARAN FISIKA DI SMK - Nuraini, Lailatul (2014)
The aims of this research were getting a display of students' science process aspec scientific literacy improvement in SMK through Science Technology Society model with scientific methods implementation. The methods was the quasi experiment research with the randomized control group pretestt posttest design. This research was implemented in one of SMK Negeri in Kota Bandung by taking two classes as samples which choosen by cluster random sampling, one class as the experiment class and the other as control class. The experiment class used the Science Technology Society model with scientific methods and the control class used the Science Technology Society model without scientific methods. The data's research was collected by using literacy science test,students and teacher respon attitude scale and observation sheet. The data were analyzed using: independent sample t-test of SPSS 16and persentage of average. The result of this research showed that the increasing of students' scientific literacy used Science Technology Society model with scientific methods higher than students' scientific literacy used Science Technology Society model without scientific methods. The N-Gain of experiment class was 0.31 and the control was 0.24 with α=0.05. Students response was agree and the teacher response strong agree that implementation of Science Technology Society model with scientific methods can be used to increase students interest and motivation, the advantage of science and technology in daily life and students' scientific literacy.